واقع توظيف استراتيجية التدريس بالقصة لتنمية المهارات اللغوية لدى تلاميذ المرحلة الابتدائية - البحراوي، فتحي مبروك (جامعة القاهرة - كلية الدراسات العليا للتربية, 2021)
هدف البحث الحالي إلى تعرف واقع ومعوقات توظيف استراتيجية التدريس بالقصة لتنمية المهارات اللغوية لدى تلاميذ المرحلة الابتدائية، والكشف عن وجود فروق ذات دلالة إحصائية حول واقع ومعوقات توظيف استراتيجية التدريس بالقصة وفقا لمتغيرات (النوع- عدد سنوات الخبرة) من وجهة نظر معلمي اللغة العربية، وقد اشتملت عينة البحث على (120) معلما ومعلمة من مدارس المرحلة الابتدائية بالمملكة العربية السعودية، واستخدم الباحث المنهج الوصفي التحليلي كمنهج للدارسة واعتمد على الاستبانة كأداة للدارسة، وقد توصل الباحث للعديد من النتائج أهمها: إن "واقع توظيف استراتيجية التدريس بالقصة في تدريس اللغة العربية لدى تلاميذ المرحلة الابتدائية من وجهة نظر معلمي اللغة العربية" جاءت بدرجة (متوسط). إن "معوقات توظيف استراتيجية التدريس بالقصة في تدريس اللغة العربية لدى تلاميذ المرحلة الابتدائية من وجهة نظر معلمي اللغة العربية" جاءت بدرجة (عالية). وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05) في آراء أفراد عينة البحث حول "معوقات توظيف استراتيجية التدريس بالقصة" وفقا لمتغير عدد سنوات الخبرة لصالح من لديهم خبرة لفترة (10) سنوات. وأوصى الباحث بالعديد من التوصيات في ضوء ما توصل إليه من نتائج أهمها: ضرورة اهتمام واضعي مناهج اللغة العربية بإثراء محتوى المنهج بالموضوعات التي تساعد على تنمية المهارات اللغوية (الاستماع-التحدث- القراءة- الكتابة) لدى التلاميذ بالمرحلة الابتدائية، وإعداد برامج وأدلة لمعلمي اللغة العربية لمساعدتهم في تطبيق استراتيجية التدريس بالقصة. The present research aimed to identify the status quo and obstacles of using the strategy of storytelling teaching to develop the language skills of elementary school pupils, and to reveal the statistically significant differences about the status quo and obstacles of using the strategy of storytelling teaching according to gender and years of experience from the point of view of Arabic language teachers. The research sample included (120) male and female elementary school teachers in Al Qassim, and the researcher used the descriptive analytical approach based on the questionnaire as the research instrument. The researcher reached several results, the most important among which were: The status quo of using the strategy of storytelling teaching in teaching Arabic to elementary school pupils from the point of view of Arabic teachers had a (medium) degree. The obstacles of using the strategy of storytelling teaching in teaching Arabic to elementary school pupils from the point of view of Arabic teachers had a (high) degree. There are statistically significant differences at (0.05) significance level, in the opinions of the sample members regarding the status quo of using the strategy of storytelling teaching, according to gender, in favor of male participants. There are statistically significant differences at (0.05) significance level, in the opinions of the sample members regarding the obstacles of using the strategy of storytelling teaching, according to years of experience, in favor of those who have 10 or more years of experience. The researcher recommended several recommendations in light of the findings, the most important of which are: the developers of Arabic language curricula must pay attention to enriching the content of the curriculum with topics that help develop the language skills (listening – speaking – reading – writing) of elementary school pupils, and to providing programs and guides for Arabic language teachers to help them apply the strategy of storytelling teaching.
Keywords: استراتيجية التدريس -- تعلم اللغات -- المهارات اللغوية -- فن القصة -- طلبة المرحلة الابتدائية